Вычисление амплитуды и начальной фазы высокочастотного колебания узкополосного радиоимпульса - Брезгунов, Александр Владимирович (НТУ "ХПИ", 2016)
Рассмотрена идея по определению амплитуды, начальной фазой высокочастотных колебаний узкополосных радиоимпульсов и амплитуды, воздействующих на них гауссовых шумов, использую значения комплексной огибающей принятого радиоимпульса и значений откликов корреляторов, с разными начальными фазами колебаний опорных генераторов.

Considered the idea to determine the amplitude and initial phase of high-frequency narrowband radio pulses and amplitude, induced Gaussian noise, using the values of the complex envelope of the received pulse and the values of the responses of the correlators with different initial phases of oscillations of the reference generator
The calculation of the amplitude and initial phase of high-frConsidered the idea to determine the amplitude and initial phase of high-frequency narrowband radio pulses and amplitude, induced Gaussian noise, using the values of the complex envelope of the received pulse and the values of the responses of the correlators with different initial phases of oscillations of the reference generatorequency fluctuations of narrowband radar pulse
Keywords: системы связи; гауссовы шумы; коррелятор; начальная фаза сигнала; опорные генераторы; signal; noise; correlator; initial phase of the signal; power.